Kepemimpinan Kiai sebagai Personal Branding Pesantren dalam Perspektif Public Relation (Humas) - Hakiki, Siti Nur (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Kiai leadership is a very influential figure in pesantren, Kiai plays an important role in progress promoting in pesantren. Leadership of the clerics in pesantren is individual leadership, which is the existence of personal Kiai in pesantren leader, in this case the research to find out how Kiai leadership is as a personal branding of pesantren in a perspective of public relations. This research is sourced from the Nadlatul Ulum Islamic boarding school in its place in Sukojember Jilbuk Jember, Nadlatul Ulum Islamic boarding school which is directly cared for by the cleric KH Moh.Tsabit Abd Hadi. KH Moh.Tsabit Abd Hadi's leadership was pesonal which became the center of Islamic boarding school progress and also the quality of the santriya. The purpose of the research results is to find out how the leadership of the clerics as personal branding in pesantren in the perspective of public relations. The description outlined from the results of the above research is how KH Mohs.Tsabit Abd Hadi's strategy is pesonal branding in the perspective of public relations in Islamic boarding schools, namely, KH Moh.Tsabit Abd Hadi through internal and external communication which communicates internal communication between Kiai and santri who were shown to be Kiai figures doubted the leadership of the pesantren while the external communication was the communication between Kiai and societies.